(untitled) (Revista Brasileira Multidisciplinar, 2019)
This study has the purpose of verifying the axial compressive strength of mortars manufactured with different additives, which are: hydrated lime, liquid detergent and white glue (PVA). For the preparation of this work, a bibliographical review was carried out and the laboratory experiment was set up. The traces of the three additives were the same, modifying only the addition of the additive. The first mortar was produced with liquid detergent, the second had the addition of white glue (PVA) and the third was using traditional hydrated lime. After production, the specimens were molded. After molding, the specimens were stored in the laboratory until adequate cure was obtained, and then they were disrupted with the aid of an automated hydraulic press. With the results of the resistance of the test specimens, it was observed that the resistance of the mortars with liquid detergent and with white glue (PVA) were equivalent, whereas the one composed of hydrated lime acquired a lower resistance.